The Epidemiology and Mechanisms of Lifetime Cardiopulmonary Morbidities Associated With Pre-Pregnancy Obesity and Excessive Gestational Weight Gain - Rastogi, Shantanu; Rastogi, Deepa (Frontiers in Cardiovascular Medicine, 2022)
In last few decades obesity has reached pandemic proportions. The global increase has corresponded with an increase in the number of pregnant women with pre-pregnancy obesity or with excessive gestational weight gain. Obesity during pregnancy is also associated with higher incidence of maternal co-morbidities such as gestational diabetes and hypertension. Both obesity during pregnancy and its associated complications are not only associated with immediate adverse outcomes for the mother and their newborns during the perinatal period but, more importantly, are linked with long-term morbidities in the offsprings. Neonates born to obese women are at higher risk for cardiopulmonary complications including respiratory distress syndrome, cardiac malformations, and non-structural cardiac issues such as elevated systolic blood pressure. Sequelae of short-term complications compound long-term outcomes such as hypertension later in life. Additional cardiopulmonary diseases associated with maternal obesity include long-term obesity, asthma during childhood and adolescence, systemic hypertension, and metabolic complications including insulin resistance and dyslipidemia. Links to adult disease such as chronic obstructive pulmonary disease and systemic hypertension have also been made with maternal obesity. Multiple mechanisms have been proposed to explain these adverse outcomes and are related to the emerging knowledge of pathophysiology of obesity in adults. The best investigated ones include the role of obesity-mediated metabolic alterations and systemic inflammation. There is emerging evidence that links metabolic and immune derangements to altered biome and highlights epigenetics as one of the intermediary mechanisms that lead to the adverse outcomes. These are initiated as part of fetal adaptation to obesity during pregnancy which are compounded by rapid weight gain during infancy and early childhood, a known complication of obesity during pregnancy. Newer evidence points towards the role of specific nutrients and changes in biome that may potentially modify the adverse outcomes.